Respons Dinamik Pelat Beton Akibat Beban Kendaraan yang Bergerak dengan Kecepatan Konstan - Liucius, Yenny Untari; Alisjahbana, Sofia W (MEDIA KOMUNIKASI TEKNIK SIPIL, 2019)
This analysis studies about the dynamic response of isotropic slab with the semi rigid type of edge conditions which is solved by the Modified Bolotin Method. The dynamic response mostly depends on the characteristics of the slab and the velocity of the transverse load acting on the slab. This analysis uses 10 km/h, 20 km/h, and 30 km/h as the velocity of the transverse load, and 110 km/h as the comparing velocity. Results show that maximum dynamic responses for each velocity does not always occur on the center of the slab, so the characteristics of the slab may be vary. The dynamic response is closest to maximum when the velocity of the load is 110 km/h because it is closer to the critical velocity of the system which is 112 km/h. This analysis assumed the slab is used for the bus’ parking ramp. Thus with the 10 km/h until 30 km/h velocity assumption for parking ramp is still quite safe because the velocity is far below the critical velocity of the system. Also the dynamic response of the system is far lower than the maximum response of slab.